Optimasi Konsentrasi Etanol Dan Perbandingan Bahan Dengan Etanol Terhadap Aktivitas Antioksidan Ekstrak Daun Beluntas (Pluchea Indica Less) Menggunakan Response Surface Methodology (RSM) - Pranantha Bistara K, I Gusti Ngurah Bagus; Suter, I Ketut; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 1 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i01.p01, 2021)
The research was conducted to obtain the optimum of ethanol concentration and comparison of material with ethanol to produced beluntas leaves extract that had the highest antioxidant activiy. Response Surface Methodology (RSM) was used for optimization of extraction conditions with experimental design was a Central Composite Design (CCD) in two factors, namely ethanol concentration and comparison of material with ethanol. The results showed that the optimum conditions of beluntas leaves extraction were at ethanol concentration 62.71% and the comparison of material with ethanol 1:10.14. In this condition, the highest antioxidant activity was obtained at 65.80% with IC 50 , extract yield, total flavonoid content, and total tannin content were 3.87 ppm, 18.20% dry weight extract, 47.05 mg QE/g dry weight extract, and 9.11 mg TAE/g dry weight extract, respectively.